Obsessive-compulsive symptoms and dissociative experiences: Suggested underlying mechanisms and implications for science and practice - Soffer-Dudek, Nirit (Frontiers in Psychology, 2023)
A strong and specific link between obsessive-compulsive disorder or symptoms (OCD/S) and a tendency for dissociative experiences (e.g., depersonalization-derealization, absorption and imaginative involvement) cannot be explained by trauma and is poorly understood. The present theoretical formulation proposes five different models conceptualizing the relationship. According to Model 1, dissociative experiences result from OCD/S through inwards-focused attention and repetition. According to Model 2, dissociative absorption causally brings about both OCD/S and associated cognitive risk factors, such as thought-action fusion, partly through impoverished sense of agency. The remaining models highlight common underlying causal mechanisms: temporo-parietal abnormalities impairing embodiment and sensory integration (Model 3); sleep alterations causing sleepiness and dreamlike thought or mixed sleep-wake states (Model 4); and a hyperactive, intrusive imagery system with a tendency for pictorial thinking (Model 5). The latter model relates to Maladaptive Daydreaming, a suggested dissociative syndrome with strong ties to the obsessive-compulsive spectrum. These five models point to potential directions for future research, as these theoretical accounts may aid the two fields in interacting with each other, to the benefit of both. Finally, several dissociation-informed paths for further developing clinical intervention in OCD are identified.